Comparing The Effects Of Artificial Intelligence (Rain Classroom), Matlab And Multimedia Teaching Platforms In Enhancing Conceptual Understanding And Innovative Thinking Among Automatic Control Principles Course Undergraduates In China - Liu, Yufei (2023)
This study aimed to investigate the effects of Artificial Intelligence (AI: Rain Classroom), MATLAB, and Multimedia teaching platforms and the students and their teachers’ perception of the use of these three teaching platforms in enhancing students' conceptual understanding and innovative thinking in the Automatic Control Principles (ACP) course. This study used a sequential explanatory mixed methods design. The quantitative data were collected using the Control System Concept Inventory (CSCI) (to measure students' conceptual understanding of ACP), and the Innovative Thinking in Education (ITE) scale (to measure students' innovative thinking ability). Using MANOVA and ANOVA analysis techniques, findings showed that there are significant differences in student's conceptual understanding of ACP and innovative thinking in the three teaching platforms studied. The results showed that the AI (Rain Classroom) teaching platform can best improve students' conceptual understanding of ACP, followed by the MATLAB teaching platform and then the multimedia teaching platform. For innovative thinking ability, the MATLAB teaching platform has the best effect, followed by the AI (Rain Classroom) teaching platform and multimedia teaching platform.